THU0402 Increased Expression of Baff Receptor on B Cells May be Implicated in Delayed Response in Systemic Lupus Erythematosus Patients Under Belimumab Therapy. (9th June 2015) - Quartuccio, L.; De Marchi, G.; Rossi, F.; Zuliani, F.; Corazza, L.; Picco, L.; Masolini, P.; Rizzolio, F.; De Vita, S.
Abstract : Background: Targeting B cell activating factor (BAFF) by belimumab is effective in systemic lupus erythematosus (SLE) (1), and leads to a partial B cell depletion (2, 3). However, which subset of B cells may be the main therapeutic target of belimumab in SLE, either why the response under belimumab is usually delayed in time is still unclear. Objectives: Our purpose was to study the effect of belimumab on different B cell subsets in SLE and in particular the expression of BAFF receptor (BAFFR) on B cells through 12 months of belimumab treatment. Methods: Seven patients with SLE (all female, age 46, 7±7, 8 years, mean disease duration of 13, 8±4, 2 years) undergoing belimumab therapy from May 2013 were studied. All patients received at least two immunosuppressors before belimumab; all patients were taking glucocorticoids at baseline (10±12 mg/day), and 6/7 were also taking at least one immunosuppressor. Mean SELENA-SLEDAI score at baseline was 9, 7±2, 7. Samples were collected and analyzed at baseline (T0), month +3 (T3), month +6 (T6), month +9 (T9) and month +12 (T12, 5 pts) for clinical and biological parameters. B cells subsets were characterized by multiparametric flowcytometry on a BD FACSCanto flowcytometer. The expression of BAFFR was also analyzed as Mean Fluorescence Intensity (MFI). Data were reported as mean ± standard error. Results: In the group of 7 SLE patients studied, a decrease of the SELENA-SLEDAI score from 9, 7±2, 7 at T0, to 6, 1±1, 9 at T3, to 5, 0±1, 0 at T6, to 4, 4±0, 8 at T9 and finally to 4, 1±0, 9 at T12 was documented. At T0 peripheral blood counts of CD19+ cells were low (median 46 cell/μl, range 1, 1-267), possibly because of the past and concomitant immunosuppressive treatments and the chronic glucocorticoids administration. CD19+CD27- cells decreased after belimumab treatment from 60±56 cell/μl at T0 to 24±14 cell/μl at T3, and then remained low over time (21±11 cell/μl at T6, 25±19 cell/μl at T9 and 23±14 cell/μl at T12). By contrast, CD19+CD27+ cells showed a transient increase as absolute counts at T6 (from 17±13 cell/μl at T0 to 23±17 cell/μl at T6), while they markedly decreased from T6 to T12 (9±7 cell/μl). BAFFR expression remained unchanged over time during therapy as percentage of B cells (mean 97±1, 7% at T0 vs. 97±2% at T9); however, a transient increase in BAFFR MFI was observed from T0 to T3 (11, 6±1, 9 to17±4, 7), and then decreased to T12 (10, 9±1, 5). The count of CD27+ B cells and the mean MFI BAFFR expression showed a similar curve over time, differently from CD19+CD27- B cells (figure 1 ). Conclusions: Hyperexpression of BAFF receptor on CD27+B cells occurs shortly after belimumab consistently with the increase in the CD27+ B cell count in the first three months of treatment. Subsequently, the BAFFR expression decrease is followed by the lowering of CD27+ B cells from T6 to T12. The intensity of BAFFR expression on CD27+ B cells may explain the pharmacodynamic of belimumab in SLE. Since belimumab acts slowly in SLE, the results observed support the hypothesis of a therapeutic effect of belimumab also on CD27+ B cells. References: Furie R et al. Arthritis Rheum 2011. Stohl W et al. Arthritis Rheum 2012. Jacobi AM et al. Arthritis Rheum 2010. Disclosure of Interest: None declared